^1-Munn ideal amenability of certain semigroup algebras - Shadab, M. (Methods of Functional Analysis and Topology, 2013)
In this paper we investigate ideal amenability of ^1(G_p), where G_p is a maximal subgroup of inverse semigroup S with uniformly locally finite idempotent. Also we find some conditions for ideal amenability of Rees matrix semigroup.